2022
DOI: 10.31557/apjcp.2022.23.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Self-Monitoring Quality of Life Intervention in Outpatients with Breast Cancer: A Preliminary Report of A Randomized Controlled Trial

Abstract: Objective: This preliminary report used data from a randomized controlled clinical trial to investigate the beneficial effects of a self-monitoring quality of life (SMQOL) intervention on communication, medical care and patient outcomes in Japanese women with breast cancer. Methods: This study compared a SMQOL intervention group with a control group that received usual care after 4 months on self-efficacy aspects of patient–physician communication among outpatients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Receiving explanation from medical personnel that numbness increases as treatments repeat and observing symptoms in the hands and legs with care Taking action to cope with numbness to maintain daily life (17) Being able to understand the transition of numbness symptoms (4)…”
Section: Categories Subcategories Example Of Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…Receiving explanation from medical personnel that numbness increases as treatments repeat and observing symptoms in the hands and legs with care Taking action to cope with numbness to maintain daily life (17) Being able to understand the transition of numbness symptoms (4)…”
Section: Categories Subcategories Example Of Codesmentioning
confidence: 99%
“…Previous studies have also reported the effects of self-monitoring on self-efficacy. [16][17][18] Self-efficacy beliefs determine how people feel, think, motivate themselves, and behave. 19 Through the self-monitoring intervention, patients recorded their symptoms, coping, cognition and mood, and investigators provided feedback based on the records.…”
Section: Promoting Coping Behaviors and Self-efficacy Through Self-mo...mentioning
confidence: 99%